Development of a customisable 3D-printed intra-oral stent for head-and-neck radiotherapy. (September 2022) - Cleland, Susannah; Crowe, Scott B.; Chan, Philip; Chua, Benjamin; Dawes, Jodi; Kenny, Lizbeth; Lin, Charles Y.; McDowall, William R.; Obereigner, Elise; Poroa, Tania; Stewart, Kate; Kairn, Tanya
Highlights: Advanced radiotherapy techniques have improved head-and-neck treatments. More improvements are possible with intra-oral stents stabilising sensitive anatomy. MRI imaging shows new modular 3D printed stents provide stable displacement. Modular stents achieve positive outcomes within standard treatment workflow. Abstract: Intra-oral stents (including mouth-pieces and bite blocks) can be used to displace adjacent non-involved oral tissue and reduce radiation side effects from radiotherapy treatments for head-and-neck cancer. In this study, a modular and customisable 3D printed intra-oral stent was designed, fabricated and evaluated, to utilise the advantages of the 3D printing process without the interruption of clinical workflow associated with printing time. The stent design used a central mouth-opening and tongue-depressing main piece, with optional cheek displacement pieces in three different sizes, plus an anchor point for moulding silicone to fit individual patients' teeth. A magnetic resonance imaging (MRI) study of one healthy participant demonstrated the tissue displacement effects of the stent, while providing a best-case indication of its comfort.